2000
DOI: 10.1515/hf.2000.021
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol/Glyoxal: A New Boron Fixation System for Wood Preservation and Dimensional Stabilization

Abstract: Anti-Swelling-Efficiency (ASE) was determined by measuring the increase in volume of treated and untreated pine blocks. Blocks were placed in a climatic chamber WTB BINDER typ KBF 115 at a temperature of 25°C and an humidity of 95 % R.H. for approxiHolzforschung / Vol. 54 / 2000 / No. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…When furfuryl alcohol was mixed with borates, boron was released to the leaching water at slower amounts, suggesting the possibility of longer protection of treated wood in service. Dauvergne et al (2000) reported that the mixture of boric acid, glycerol, and glyxocal impregnated Wood pine results in less boron leaching due to formation of complexes. Lloyd et al (1990) reported that the addition of polyols to borate solutions greatly increased the boron stability through borate/polyolchelate complexion.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
See 1 more Smart Citation
“…When furfuryl alcohol was mixed with borates, boron was released to the leaching water at slower amounts, suggesting the possibility of longer protection of treated wood in service. Dauvergne et al (2000) reported that the mixture of boric acid, glycerol, and glyxocal impregnated Wood pine results in less boron leaching due to formation of complexes. Lloyd et al (1990) reported that the addition of polyols to borate solutions greatly increased the boron stability through borate/polyolchelate complexion.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Many of the metallic oxides commonly used in water-borne preservative formulations react with the cell wall components by undergoing hydrolytic reduction upon contact with wood carbohydrates. This process, known as fi xation, oxidizes the wood cell wall component and may reduce wood strength (Dauvergne et al, 2000). The relative impact of various water-borne preservative systems is directly related to the preservative chemistry and severity of its fi xation/precipitation reaction (Winandy, 1996).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Several research groups have successfully worked on fixing boron and other metals in wood (Thevenon et al 1998;Toussaint-Dauvergne et al 2000;Xie et al 1995) but no definitive solutions were found. It is only recently that the fixation of boron with cross-linkable flavonoids has been further investigated (Thevenon et al 2010;Tondi et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of wood with boron-containing inorganic (Cockcroft and Levy 1973;Pizzi and Baecker 1996;Toussaint-Dauvergne et al 2000) or organic chemicals (Howell 1988;Lloyd and Deane-Wray 1995;Yalinkilic et al 1998a) belong to the remedies. The treatment of wood with boron-containing inorganic (Cockcroft and Levy 1973;Pizzi and Baecker 1996;Toussaint-Dauvergne et al 2000) or organic chemicals (Howell 1988;Lloyd and Deane-Wray 1995;Yalinkilic et al 1998a) belong to the remedies.…”
Section: Introductionmentioning
confidence: 99%